Evaluation of the essential oil and study of cold conservation of Cymbopogon citratus cultivated in the region of the Quindío (Revista de Investigaciones Universidad del Quindío, 2010)
The study of Cymbopogon citratus also known as "lemon grass", was divided into two parts: the extraction of essential oil from fresh leaves, dried by hot air (DHA) and dried in a greenhouse (DG) using two extraction methods such as steam distillation (SD) and microwave-assisted hydrodistillation (MWHD), obtaining the best performances by the method of MWHD with the leaves dried by DHA in a time of 90min. Evaluation of oil by gas chromatography-mass spectrometry (GC-MS) showed that the main compounds in the oil are geranial and eral. The second part was to study the conservation of the leaves of C. citratus in a cold environment (12°C) and packaged in foil pouches and glass flasks, monitoring the parameters of acidity, pH, water activity and color, finding no significant difference between glass and aluminum containers, so it is recommended to use foil pouches for storage and maintenance, due to its facilities in terms of volume and economy.
Keywords: Cold Conservation; Cymbopogon citratus; Esential Oil